53.2k views
0 votes
Name the postulate or theorem you can use to prove NPM=OMP

Name the postulate or theorem you can use to prove NPM=OMP-example-1
User Gope
by
5.0k points

1 Answer

3 votes

Answer:

ΔNPM and ΔOMP by SAS postulate

B is correct

Explanation:

In ΔNPM and ΔOMP

NP = OM (Given)

∠NPM = ∠OMP (Given)

PM = MP ( Common )

So, ΔNPM ≅ ΔOMP by SAS property of concurrency.

ΔNPM and ΔOMP are congruent because their two side and angle between them are equal.

Therefore, SAS postulate use here

Hence, ΔNPM and ΔOMP by SAS postulate

User Peace Ngara
by
6.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.